2015
DOI: 10.2340/00015555-1940
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Victims of Childhood Vitiligo: Impact on Parents’ Mental Health and Quality of Life

Abstract: This study aims to assess the impact of childhood vitiligo on the psychological status and quality of life of their parents, and to determine how this varies according to their children's disease condition. The study included 50 families of children with vitiligo (a total of 75 participants) and 50 families of normal children (a total of 79 participants). The psychosocial impact of the disease on parents was measured using the Self-rated Health Measurement Scale (SRHMS) and the Dermatitis Family Impact Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 12 publications
1
34
0
4
Order By: Relevance
“…This study is the first to describe QoL in parents of children with vitiligo in the United States. The only other study that described QoL in parents of children with vitiligo previously was done in China [10]. This study used different measures, the Self-rated Health Measurement scale (SRHMS) and the Dermatitis Family Impact Questionnaire (DFIQ), and showed that parents of children with vitiligo have significant psychological problems and poor QoL compared to parents of unaffected children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to describe QoL in parents of children with vitiligo in the United States. The only other study that described QoL in parents of children with vitiligo previously was done in China [10]. This study used different measures, the Self-rated Health Measurement scale (SRHMS) and the Dermatitis Family Impact Questionnaire (DFIQ), and showed that parents of children with vitiligo have significant psychological problems and poor QoL compared to parents of unaffected children.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pediatric patients with chronic disease like psoriasis, alopecia areata and atopic dermatitis, this burden has been shown to also involve the lives of parents and other primary caregivers [4][5][6][7]. To date, in the study of vitiligo, assessments of QoL impact have focused on pediatric patients but not on their caregivers [2,3,[8][9][10]. To address this knowledge gap, the purpose of this study was to examine the QoL impact in parents of children with vitiligo using two externally validated QoL tools, the Quality of Life in a Child's Chronic Disease Questionnaire (QLCCDQ) and the Family Dermatology Life Quality Index (FDLQI) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…An Arabic version and a Ukrainian version have been published. The DFI has been used in many studies . A review of the use of the instrument showed that 26 studies correlated the DFI to other instruments, demonstrating its convergent validity.…”
Section: Resultsmentioning
confidence: 99%
“…The DFI has been used in many studies. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] A review of the use of the instrument 46 showed that 26 studies correlated the DFI to other instruments, demonstrating its convergent validity. Internal consistency was demonstrated by three studies, with Cronbach's alpha ranging from 0.85 to 0.90, and test-retest reliability by one study.…”
Section: Family Dermatology Life Quality Index (Fdlqi)mentioning
confidence: 99%
“…El vitiligo puede llegar a ser psicológicamente devastador y un estigma, especialmente en las personas de piel oscura. Mediante encuestas de calidad de vida y autopercepción, se ha demostrado que los pacientes con vitiligo y sus familiares presentan alteraciones psicológicas (31) . Los afectados suelen padecer con mayor frecuencia depresión y disminución de la calidad de vida; los adolescentes con compromiso extenso en la cara o afectación genital, presentan alteraciones escolares, falla escolar, baja autoestima y dificultad en su desarrollo sexual (32) .…”
Section: Trastornos Psicológicos Asociados Con El Vitiligounclassified